Psychometric properties of the normative deviance scale in youths - Garrido, Sebastián Jesús (2019)
Background: Antisocial behavior refers to a set of acts that violate the rules established for the coexistence of society. One of the self-report measures to assess this type of behavior is the normative deviance scale (NDS). Objective: Considering that in the Argentine context no studies on the psychometric properties of the scale were found, the present study aimed to analyze the psychometric properties of the scale in a sample of Argentine youths. Method: To this end, a sample of 794 participants aged between 18 and 25 years was collected. A confirmatory factor analysis was performed; the composite reliability was calculated; and the convergent, discriminant and concurrent validity was assessed (using a self-control scale). In addition, the invariance of the factorial structure of the scale was analyzed. Results: The results confirmed the original factorial structure of the scale with no factorial equivalence across the assessed groups regarding the sex. Also, the results showed adequate psychometric properties for most dimensions which make up the instrument. Conclusions: Findings, limitations and further lines of research are discussed.